Target stores : strategic brand alliance exercise - Tybout, Alice M. (London : Kellogg School of Management, 2007)
The case outlines how Target has achieved successful strategic brand alliances in the past and asks the student to consider what criteria Target should use for new potential brand alliances.
Originally published in Tybout, A. M. (2007). Target stores: Strategic brand alliance exercise. 5-407-750. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Target Corporation; Strategic alliances (Business)